INTERAKSI AKTOR DALAM PROSES PERUMUSAN KEBIJAKAN PUBLIK (STUDI KASUS KEBIJAKAN PERMUKIMAN DI PROVINSI DKI JAKARTA) - Mahmud, Favian Laksono; Ardianto, Hendra Try (Journal of Politic and Government Studies, 2020)
This study wanted to find out how the interaction between actors in the process offormulating public policies, especially settlement policies in DKI Jakarta Province. The methodused in this study is a qualitative method with a case study approach, which is an approach todeepen a unique case. The process of formulating public policy is a process of interdependencebetween the actors involved and bargaining between actors occurs. The results of this study findpolitical contracts as a momentum of interaction between actors and the process of interactionthat occurs between policy actors is cooperative and accommodative interaction. So theconclusion of this study is the cooperative and accommodative interaction between actors tends tobe effective in producing settlement policy decisions without evictions in DKI Jakarta Province.Keywords: Settlement Policy, Political Contract, Actors Interaction, The Formulation of PublicPolicy Process